MEMAHAMI NARASI KOMUNIKASI PENGAMBILAN KEPUTUSAN UNTUK TIDAK MENIKAH PADA PEREMPUAN - Alya Azma Fazira; Lintang Ratri Rahmiaji; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
The patriarchal culture that has developed in Indonesia deprives women of the freedom to choose their own path in life, one of which is the decision not to get married. Women, who are often confined to domestic work, are expected to marry, making the decision not to marry a difficult one due to the social pressure they face. Therefore, this study aims to narrate the experiences of informants who eventually decided not to marry. Three women were interviewed to trace their life journeys, both before and after making the decision not to marry. This research utilizes Labov's narrative method to chronicle the sequence of events experienced by each informant. The results of the study indicate that the decision not to marry occurs when women realize that marriage is a choice. It explores how women, living in a social construct that forces them to marry, are able to resist dominant culture and fight for their right to choose their own path in life. The study also reveals that the decision-making process is not instantaneous. Each informant had unique experiences observing marriage and romance within their family environment, such as parental infidelity, family economic difficulties, and failed relationships. These experiences ultimately led to a negative perception of married life, which influenced their decision not to marry. The decision-making process not to marry occurs when informants are confronted with choices and questions from their social environment regarding marriage. It is at that moment when the informants express their decision and explain the unique experiences that underlie their choice not to marry. However, not all women openly express their decision in public. The study also demonstrates that women who decide not to marry often face rejection, stigmatization, mockery, and discrimination from their social environment, which considers their decision irrational for women. Some informants choose to defend themselves and explain their perspectives that inform their decision. However, there are also informants who choose to remain silent and provide brief responses when faced with social pressure.